the prevalence of Capillaria sp in chickens in Hama Governorate (Journal of Hama University, 2026)
This study aimed to investigate the prevalence of Capillaria spp. infections in chickens in Hama Governorate, Syria, and to analyze the factors influencing infection rates. A total of 1,601 fecal samples were collected from local chickens and intensively reared commercial hybrid chickens between March 4, 2024, and March 4, 2025. Laboratory examination was performed using gross examination, direct smear, and flotation concentration methods. Data were statistically analyzed using the Chi-Square test at a significance level of P
Keywords: Keywords: Capillaria spp, local chicken, hybrid chicken.